Statistical Analysis of Hydrodynamic Forces in Power-Law Fluid Flow in a Channel: Circular Versus Semi-Circular Cylinder - Mahmood, Rashid; Majeed, Afraz Hussain; Tahir, Muhammad; Saddique, Imran; Hamadneh, Nawaf N.; Khan, Ilyas; Mehmood, Asif (Frontiers in Physics, 2022)
This numerical study is about the steady incompressible non-Newtonian fluid flow in a channel with static obstacles. The flow field is governed by the Generalized Navier-Stokes equations incorporating the constitutive relation of power-law fluids. Three cases are considered: 1) circular obstacle (C1), 2) semicircular obstacle (C2), and 3) both circular and semicircular obstacles. A range of values of the power-law index 0.3≤n≤1.7 are considered at Re=20 to check the impact of shear-thinning and shear-thickening viscosity on the drag and lift coefficients. The correlation between drag and lift coefficients is calculated against the power-law index. The simulated results of velocity and pressure are investigated at different sections of the channel. Benchmark results of drag and lift for the Newtonian fluid are reproduced as a special case. A strong positive correlation is observed between drag and lift coefficients in the case of a single obstacle, while in the case of dual obstacles and inverse correlation, drag and lift coefficients have been found.